2020
DOI: 10.1111/febs.15360
|View full text |Cite
|
Sign up to set email alerts
|

CRY1‐CBS binding regulates circadian clock function and metabolism

Abstract: Circadian disruption influences metabolic health. Metabolism modulates circadian function. However, the mechanisms coupling circadian rhythms and metabolism remain poorly understood. Here, we report that cystathionine b-synthase (CBS), a central enzyme in one-carbon metabolism, functionally interacts with the core circadian protein cryptochrome 1 (CRY1). In cells, CBS augments CRY1-mediated repression of the CLOCK/BMAL1 complex and shortens circadian period. Notably, we find that mutant CBS-I278T protein, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Third, when compared with CRY2, CRY1 is a more potent repressor of BMAL1/CLOCK-transactivation on E-boxes (22,23). Finally, CRY1 specifically interacts with Cystathionine β-synthase by regulating one-carbon and transsulfuration pathways (24). All these studies show functional differences between the CRYs in the circadian clock mechanism.…”
mentioning
confidence: 89%
“…Third, when compared with CRY2, CRY1 is a more potent repressor of BMAL1/CLOCK-transactivation on E-boxes (22,23). Finally, CRY1 specifically interacts with Cystathionine β-synthase by regulating one-carbon and transsulfuration pathways (24). All these studies show functional differences between the CRYs in the circadian clock mechanism.…”
mentioning
confidence: 89%
“…43 Moreover, although the functions of Cry1 and Cry2 in the core circadian clock were initially thought to be redundant, they have distinct and separable roles in the circadian molecular clock 44 and peripheral metabolism rhythms. 45 For experimental and drug design, it would be important in the future to modulate both Cry1 and Cry2 simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In CRY1-KO mice, reduced cystathionine b-synthase (CBS) activity levels were reported that were rescued by adding exogenous CRY1. CRY1-induced CBS activation led to post-translational switch that modulated metabolism [276]. Interestingly, the circadian regulator Nocturnin, a rhythmic gene encoding a deadenylase thought to be involved in the removal of poly(A) tails, controls glucose and lipid metabolism [277], as well as metabolic adaptation in brown adipose tissue [278].…”
Section: Peripheral Clocks Control Cell and Organ Physiology: Lessonsmentioning
confidence: 99%